Etnomodelagem no contexto do cultivo de hortaliças na Comunidade de Tamatáquara do Maú - Marapanim/PA - FERREIRA, Juliana Victória de Lima (2024)
The main objective of this work is to analyze the use of mathematical ethnomodels in the local practice of vegetable cultivation. Therefore, the research was carried out in the com munity of Tamataquara do Maú, in the municipality of Marapanim, in the state of Pará. In this activity, we sought to recognize what informal mathematical knowledge can be used in the mathematization process of mathematical modeling in this community. Subsequen tly, the data was produced based on observation of vegetable cultivation activities, and also through interviews with the producer owners in that community. Data analysis shows that the research achieved its objectives, according to the information obtained, identifying which mathematical models found can contribute to considerable and contextualized learning th rough Ethnomodeling through Mathematical Modeling.